2022
DOI: 10.1186/s12891-022-04994-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key biomarkers in steroid-induced osteonecrosis of the femoral head and their correlation with immune infiltration by bioinformatics analysis

Abstract: Objective This study aimed to identify key diagnostic markers and immune infiltration of (SONFH) by bioinformatics analysis. Methods Related SONFH datasets were downloaded from the Gene Expression Omnibus (GEO) database. First, we identified the differentially expressed genes (DEGs) and performed the functional enrichment analysis. Then weighted correlation network analysis (WGCNA) and the MCODE plug-in in Cytoscape were used to identify the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…Microsoft Excel was used to segregate the relevant physiological data and tables. Barplot in R (4.0.2) was used to draw the histogram (mean ± standard error (SE); SE = SD/sqrt (n)), cor to draw the correlation analysis chart (Zhao et al, 2022), and gplots and pheatmap to draw the heat map after the FPKM values of gene expression in three time periods were standardized.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…Microsoft Excel was used to segregate the relevant physiological data and tables. Barplot in R (4.0.2) was used to draw the histogram (mean ± standard error (SE); SE = SD/sqrt (n)), cor to draw the correlation analysis chart (Zhao et al, 2022), and gplots and pheatmap to draw the heat map after the FPKM values of gene expression in three time periods were standardized.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…Therefore, we hypothesize that in the pathogenesis of SONFH, an imbalance in copper metabolism may cause disordered immune regulation in the body and thus induce femoral head necrosis. Recently, studies have shown that immune cell infiltration is associated with the progression of SONFH [ 35 , 60 , 61 ]. In the present study, we concluded that PNP expression had a notable and the strongest negative association with plasmacytoid dendritic cell infiltration, while PNP expression had a notable and the strongest positive association with CD56 bright natural killer cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…64 During the progression of GIONFH, large numbers of chronic inflammatory cells may infiltrate into the peripheral blood and necrotic zone. 65 Multiple studies [66][67][68] evaluated immune infiltration in serum by analyzing GSE123568 which enrolled thirty patients with GIONFH and ten healthy controls, and found decreased infiltration of memory B cells and activated dendritic cells. It could be noticed that macrophages (M0, M1 and M2) were not significantly enriched in the GIONFH group.…”
Section: Immune Infiltration and Macrophage Distribution In Gionfh Im...mentioning
confidence: 99%